2009
DOI: 10.1111/j.1365-2966.2009.15519.x
|View full text |Cite
|
Sign up to set email alerts
|

Spread spectrum for imaging techniques in radio interferometry

Abstract: We consider the probe of astrophysical signals through radio interferometers with small field of view and baselines with non-negligible and constant component in the pointing direction. In this context, the visibilities measured essentially identify with a noisy and incomplete Fourier coverage of the product of the planar signals with a linear chirp modulation. In light of the recent theory of compressed sensing and in the perspective of defining the best possible imaging techniques for sparse signals, we anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(117 citation statements)
references
References 24 publications
2
115
0
Order By: Relevance
“…For example, chirp sequences were applied to radio interferometry in [31], where the sensing matrix was constructed in a different way, namely, it was the product of a rectangular binary matrix M, Fourier matrix F, diagonal matrix C implementing chirp modulation and diagonal matrix D implementing the primary beam. The coherence was analyzed when Ψ is formed by Gaussian waveforms.…”
Section: Connections With Existing Workmentioning
confidence: 99%
“…For example, chirp sequences were applied to radio interferometry in [31], where the sensing matrix was constructed in a different way, namely, it was the product of a rectangular binary matrix M, Fourier matrix F, diagonal matrix C implementing chirp modulation and diagonal matrix D implementing the primary beam. The coherence was analyzed when Ψ is formed by Gaussian waveforms.…”
Section: Connections With Existing Workmentioning
confidence: 99%
“…This is a convex relaxation of Equation (1) and can be transformed into the Lagrange form: (Honma et al 2014;Akiyama et al 2016;Ikeda et al 2016) and found that LASSO can potentially reconstruct structure on scales ∼4 times finer than D max l (Honma et al 2014). Techniques of compressed sensing are beginning to be used in other fields of radio interferometry 15 after pioneering work by Wiaux et al (2009a) and Wiaux et al (2009b) (see Garsden et al 2015, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…In their paper, they did not consider a sparse representation that is appropriate for extended sources in the sky. In a subsequent paper, Wiaux and other authors propose a new spread spectrum technique for radio interferometry (Wiaux et al 2009b) by using the non-negligible and constant component of the antenna separation in the pointing direction. Moreover, in their second paper, they assumed that any kind of astrophysical structure consist of Gaussian waveforms of equal size and similar standard deviation.…”
Section: Introductionmentioning
confidence: 99%